PENINGKATAN RASIONALITAS PENGGUNAAN OBAT MELALUI KEGIATAN EDUKASI KEPATUHAN MINUM OBAT MASYARAKAT DI RT 06 ALALAK UTARA, BANJARMASIN UTARA - Joko Priyanto Wibowo; Qadhy Kamil Al-Banjarie; Adinda Wulandari; Akhmad Fadillah Mursyid; Stevani Angelica; Vidya Azelia Sherlinda (JURNAL PENGABDIAN MANDIRI, 2026)
Medication adherence issues in the community continue to challenge therapeutic success. This community service was conducted to improve understanding among residents of RT 06 RW 01, North Alalak Sub-district, North Banjarmasin regarding the importance of medication adherence. The target participants were 24 adult residents selected for their role in household medication decision-making. Implementation occurred in December 2025 through three stages: preparation, execution and evaluation. Initial observations revealed that most residents discontinued medication when symptoms improved without completing prescribed courses. The intervention was delivered interactively using PowerPoint, educational videos and leaflets, complemented by discussion and Q&A sessions. Knowledge levels were measured using pre-test and post-test, while participant satisfaction was assessed through Likert scale questionnaires. Results showed average score improvement from 4.0 to 7.04, representing a 76% increase. Participant satisfaction reached 4.25 on a scale of 5. Despite significant knowledge improvement, continued support remains necessary to ensure sustainable behavioral changes in daily medication practices within the community